2017
DOI: 10.3727/096504017x14841698396829
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-21 Inhibits the Apoptosis of Osteosarcoma Cell Line SAOS-2 via Targeting Caspase 8

Abstract: Currently, multiple microRNAs (miRNAs) have been found to play vital roles in the pathogenesis of osteosarcoma. This study aimed to investigate the role of miR-21 in osteosarcoma. The level of miR-21 in 20 pairs of osteosarcoma and corresponding adjacent tissues was monitored by qPCR. Human osteosarcoma cell line SAOS-2 was transfected with either miR-21 mimic or miR-21 inhibitor, and then cell viability, survival, and apoptosis were measured by MTT, colony formation assay, and flow cytometry. A target of miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…4E and F , the expression of miR-21-5p was significantly increased compared with the human osteoblast cell line hFOB 1.19 and adjacent normal tissues. This result is consistent with a previous study ( 24 ). Moreover, we examined the potential correlation among the expression levels of XIST and miR-21-5p, and an inverse correlation between XIST and miR-21-5p expression levels was observed ( Fig.…”
Section: Resultssupporting
confidence: 94%
“…4E and F , the expression of miR-21-5p was significantly increased compared with the human osteoblast cell line hFOB 1.19 and adjacent normal tissues. This result is consistent with a previous study ( 24 ). Moreover, we examined the potential correlation among the expression levels of XIST and miR-21-5p, and an inverse correlation between XIST and miR-21-5p expression levels was observed ( Fig.…”
Section: Resultssupporting
confidence: 94%
“…MicroRNAs are endogenous, small, non-coding RNAs that regulate gene expression through binding to the 3′untranslated region of target mRNAs [3]. MicroRNA-21(miR-21) is considered as an oncogene, and the up-regulation of it has been reported in a wide range of solid and leukaemic cancers such as colon, gastric, breast and pancreatic cancers [4]. Overexpression of miR-21 also inhibited apoptosis in osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies also reported that HNK induces apoptosis and G 1 cell cycle arrest in various types of cancer cell ( 39 42 ). Furthermore, miR-21 has been identified as an important regulator of diverse cellular functions via the regulation of cancer cell growth ( 43 45 ). However, the possible molecular mechanism underlying HNK-induced apoptosis of human OS cells requires further research.…”
Section: Discussionmentioning
confidence: 99%